POTENSI MINAT GEN Z TERHADAP PRODUK INTERNET BANKING: Studi Pada Bank Jago di Kota Semarang - Kim Meredith Dionese; Setyo Pantawis (UNPERBA, 2026)
Digital banks in Indonesia have continued to show growth in recent years. One example is Bank Jago, which has seen an increase in the use of its internet banking services every year. However, this increase in the number of users still faces various complaints from consumers. This study aims to analyze the influence of convenience, security, and service features on the interest in using Bank Jago's internet banking services among Generation Z in Semarang City. This research method uses a quantitative approach with a sample of 97 people taken with a purposive sampling model. Data analysis uses multiple linear regression methods with SPSS statistical software 30. The results of this study indicate that the variables of convenience, security, and service features have a positive and significant effect on interest.